Web-Based Interventions for Individuals who Committed Sexual Offenses Against Children: Development, Evaluation, and Implementation - Schröder, Sonja (Criminal justice and behavior, 2023)
Web-based interventions (WBIs) have become increasingly important in mental health treatment. At the same time, WBIs for individuals who committed sexual offenses against children (ICSOC) are increasingly being developed and implemented. Despite this trend, it is unclear which treatment components make WBIs for ICSOC effective and what needs to be considered for successful implementation. Moreover, only few evaluation studies are available. The goal of this viewpoint paper, that includes a comprehensive literature review, is to provide criteria for the development, evaluation, and implementation of WBIs for ICSOC or for individuals who feel at risk of committing sexual offenses against children. The criteria are drawn from guidelines for WBIs in general psychiatry, in forensic psychiatry, and for ICSOC. For the latter, an overview of current WBIs for ICSOC and for individuals who feel at risk of committing sexual offenses against children will be provided.